2002
DOI: 10.1210/endo.143.1.8602
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin, A New Gastrointestinal Endocrine Peptide that Stimulates Insulin Secretion: Enteric Distribution, Ontogeny, Influence of Endocrine, and Dietary Manipulations

Abstract: Ghrelin, an endogenous ligand for the GH secretagogue receptor was characterized recently from extracts of rat stomach. We describe the enteric distribution of ghrelin, ontogeny of stomach ghrelin gene expression, effects of dietary and endocrine manipulations, and vagotomy on stomach ghrelin mRNA and peptide levels and secretion in the rat. Ghrelin expression was examined by Northern blotting. Tissue and plasma ghrelin levels were measured by RIA. A gradient of ghrelin production occurs in the rat gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
138
4
12

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(163 citation statements)
references
References 24 publications
9
138
4
12
Order By: Relevance
“…Rodent studies examining the relationship between vagal activity and fasting ghrelin secretion have provided conflicting data. Electrical stimulation of the vagus nerve in fasting rodents caused an increase in circulating concentrations of ghrelin (Murakami et al 2002), whereas a separate study showed an elevation in ghrelin concentrations following vagotomy (Lee et al 2002). However, it must be noted that the measurements of ghrelin were made 14 days after vagotomy, representing long-term changes, rather than the acute changes currently observed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rodent studies examining the relationship between vagal activity and fasting ghrelin secretion have provided conflicting data. Electrical stimulation of the vagus nerve in fasting rodents caused an increase in circulating concentrations of ghrelin (Murakami et al 2002), whereas a separate study showed an elevation in ghrelin concentrations following vagotomy (Lee et al 2002). However, it must be noted that the measurements of ghrelin were made 14 days after vagotomy, representing long-term changes, rather than the acute changes currently observed.…”
Section: Discussionmentioning
confidence: 97%
“…The vagus nerve has been shown to be intrinsically linked to both ghrelin regulation (Lee et al 2002) and action (Masuda et al 2000). Vagotomy elevates plasma ghrelin significantly (Lee et al 2002), whereas electrical stimulation of the vagus nerve tends to decrease ghrelin in rats (Murakami et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, granted that such a mechanism is operative, it would not account for the almost 2·5-fold rise in circulating ghrelin concentrations that we have encountered in our study. It appears more likely that starvation and/or a low protein intake was stimulating secretion of gastric ghrelin in these subjects (Lee et al 2002). Irrespective of the underlying mechanism(s), refusal of food in A-AN patients, who have high circulating concentrations of ghrelin and, presumably, high and low hypothalamic NPY and leptin functions respectively (Baranowska et al 2001) bespeaks a downregulation of the appetite-regulating system or a predominance of a central inhibitory system of energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory signals seem to include leptin, insulin, GH and insulin-like growth factor-I (IGF-I), and a high-fat diet, whereas fasting and a low-protein diet have been related to increased plasma concentrations of ghrelin (Horvath et al 2001, Toshinai et al 2001, Lee et al 2002. Interestingly, recent data indicate that ghrelin is downregulated in human obesity which is also accompanied by reduced GH levels (Scacchi et al 1999) and, conversely, plasma ghrelin levels are elevated in anorexia nervosa (AN), a GH hypersecretory state (Müller et al 1995), and return to normal levels after partial weight recovery (Otto et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The onset of insulin resistance and compensatory hyperinsulinemia in obesity is probably the reason for the suppression of ghrelin levels (13). Ghrelin has been characterized in earlier studies as an enhancer of insulin secretion (14,15), while more recent studies with mice have shown that the antagonism of its effects could promote the secretion of insulin and prevent glucose intolerance induced by a high-fat diet (16,17). …”
Section: Introductionmentioning
confidence: 99%